Epidemiology and its results in hip fractures followed in postoperative intensive care - Emel Yildiz; Murat Emre Tokur; Özlem Arik; Ayşe Yildirimer; Halil Ibrahim Yildiz; Canan Balci (Medicine, 2026)
The global proportion of individuals aged ≥ 65 years is approximately 9%, and hip fractures (HFx) represent one of the most common and serious injuries in this population. This study retrospectively evaluated postoperative intensive care unit (ICU) admissions among patients with HFx, focusing on 30-day, 90-day, and 1-year mortality outcomes. This retrospective study included patients with HFx who were admitted to the ICU after surgery. Collected data included demographic characteristics (age and gender), admission diagnosis, comorbidities, ICU length of stay (LOS), Acute Physiology and Chronic Health Evaluation (APACHE) II scores, American Society of Anesthesiologists score, LOS, 30-day/ 90-day/1-year mortality, day of surgery, and the type anesthesia used. The mortality rate were 34.4% at 30-days 41.3% at 90 days and 24.1% at 1 years after surgery. Patients who died had significantly higher mean age, Acute Physiology and Chronic Health Evaluation II scores, ICU LOS, and total hospital stay. Our findings suggest that postoperative ICU admission criteria for patients with HFx should be reconsidered. The results also emphasize the importance of optimizing ICU LOS in this patient group. Further prospective studies are needed to clarify whether prolonged ICU stay contributes to increased mortality or reflects greater baseline severity.